2018
DOI: 10.1016/j.virol.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing replication kinetics and plaque production of type I feline infectious peritonitis virus in three feline cell lines

Abstract: Investigating type I feline coronaviruses (FCoVs) in tissue culture is critical for understanding the basic virology, pathogenesis, and virus-host interactome of these important veterinary pathogens. This has been a perennial challenge as type I FCoV strains do not easily adapt to cell culture. Here we characterize replication kinetics and plaque formation of a model type I strain FIPV Black in Fcwf-4 cells established at Cornell University (Fcwf-4 CU). We determined that maximum virus titers (>10 pfu/mL) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…1C). In AK-D 2.2 cells, plaques were more easily identified at 72 hpi, and plaque sizes were comparable to those on Fcwf-4 CU cells at 48 hpi as we recently reported (O'Brien et al, 2018). It was difficult to accurately determine virus titer using wildtype AK-D cells, as the plaques were too small to count accurately at both time points and led to an underestimation of PFU/mL.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…1C). In AK-D 2.2 cells, plaques were more easily identified at 72 hpi, and plaque sizes were comparable to those on Fcwf-4 CU cells at 48 hpi as we recently reported (O'Brien et al, 2018). It was difficult to accurately determine virus titer using wildtype AK-D cells, as the plaques were too small to count accurately at both time points and led to an underestimation of PFU/mL.…”
Section: Resultssupporting
confidence: 70%
“…To our knowledge, such IFN-nonresponsive feline cell lines were not available and studies using gene-modifying tools such as Crispr/Cas had not been performed in feline cells permissive to FCoVs. In a previous study, we characterized the growth kinetics of FIPV Black in AK-D and Fcwf-4 CU cells and demonstrated that rapid growth of wild-type serotype I FIPV could be achieved given the right cell type and conditions (O'Brien et al, 2018). However, these cells still produced IFN upon stimulation suggesting that neither cell line would be appropriate for recovery of viruses attenuated by deletion on IFN antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, entry efficiencies of Scotophilus bat CoV-512 and SARS-CoV in 11 different cells were evaluated using a lentivirus-based pseudovirus system. HEK-293T cells were selected as they have been used for the production of pseudoviruses; additionally, several cell lines were selected because they were used for the isolation and maintenance of viruses in other studies, such as Vero and PK15 cells for PEDV [17], MDCK cells for influenza viruses [18], and Fcwf-4 cells for FCoV [19]. Given that CoVs tend to replicate in the epithelial cells of enteric and respiratory tracts, Caco-2 and IEC-6 were selected.…”
Section: Discussionmentioning
confidence: 99%